1973
DOI: 10.1037/h0035412
|View full text |Cite
|
Sign up to set email alerts
|

Personality differences among men in selected Air Force specialties.

Abstract: Job placement based on aptitude has provided the human resources necessary to perform the Air Force mission but has not produced a work force that is satisfied with the duty assignments that are made. A consideration of enlistee personality and interests might refine this job placement system. The purpose of this study was to determine if personality differences exist among men in selected Air Force specialties using Holland's Vocational Preference Inventory (VPI). The specialties were compared further by mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1976
1976
1978
1978

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Several methods have been used to investigate Holland's environment formulations. The most common method was to compare personality measurements on employed workers in occupations representing environment models (Andrews, 1973;Bates, Parker, & McCoy, 1970;Fabry, 1975Fabry, , 1976Fishburne & Walsh, 1976;Gaffey & Walsh, 1974;Harvey & Whinfield, 1973;Horton & Walsh, 197,6;Hughes, 1972;Lacey, 1971;Morrison & Arnold, 1974;O'Brien & Walsh, 1976;Osipow, 1970;Schuldt & Stahmann, 1971;Walsh, Horton, & Gaffey, 1977;Werner, 1969;Wigington & Apostal, 1973). The results of these studies have generally been in the direction hypothesized by Holland's theory.…”
mentioning
confidence: 99%
“…Several methods have been used to investigate Holland's environment formulations. The most common method was to compare personality measurements on employed workers in occupations representing environment models (Andrews, 1973;Bates, Parker, & McCoy, 1970;Fabry, 1975Fabry, , 1976Fishburne & Walsh, 1976;Gaffey & Walsh, 1974;Harvey & Whinfield, 1973;Horton & Walsh, 197,6;Hughes, 1972;Lacey, 1971;Morrison & Arnold, 1974;O'Brien & Walsh, 1976;Osipow, 1970;Schuldt & Stahmann, 1971;Walsh, Horton, & Gaffey, 1977;Werner, 1969;Wigington & Apostal, 1973). The results of these studies have generally been in the direction hypothesized by Holland's theory.…”
mentioning
confidence: 99%
“…Similar studies include Horton and Walsh (1976), Walsh, Horton, and Gaffey (1977), and Wigington and Apostal (1973)» as well as many other studies. Via this method, support for Holland's formulations were generally found.…”
Section: Use Of Information On the Environment's Populationmentioning
confidence: 59%
“…Wasserman (1974), in using Holland's theory to test the personality and vocational choices of adolescent girls, concluded that it was more appropriate for career-oriented than for homemaker-oriented women. Wigington and Apostal (1973), in testing personality differences among men in selected Air Force specialties, found that the realistic and investigative scales discriminated among four Air Force specialties for men who reenlisted in the Air Force.…”
Section: A Person's Behavior Is Determined By An Interactionmentioning
confidence: 99%